CTLA-4 +49A/G and -318 C/T polymorphisms and cytokines level on inhibitors development of haemophilia A among different ethnicity in Malaysia - Nadarajan, Anantha Kummar; KN Vaiappuri, VS Selvavani; Karim, Faraizah; Abu Bakar, Suhaili; Md Noor, Sabariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Haemophilia A (HA) is an inherited X-chromosome recessive disorder characterized by the deficiency of factor VIII (FVIII). About 25-30% of HA patients which received FVIII concentrate developed inhibitors towards FVIII. Ethnicity has been associated as a predisposing factor for the formation of FVIII inhibitors. This study character- izes the polymorphism of +49A/G and -318C/T of Cytotoxic T-Lymphocytes Antigen 4 (CTLA-4) which relates to the development of inhibitors among Malaysian HA patients of Malay, Chinese and Indian ethnicity. Cytokines level of tumour necrosis factor alpha (TNFα), interleukin 4 (IL-4) and interleukin 10 (IL-10) were also measured to assess the link to inhibitors development. Method: Severe HA patients with and without inhibitor who were being treated at the National Blood Centre, Kuala Lumpur were recruited and consented where their collected blood was genotyped for both polymorphisms using the Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) and their cytokines levels were measured using the Enzyme-linked Immunosorbent Assay (ELISA). Results: Analysis of the total 64 respondents who fulfilled the study criteria found polymorphisms of CTLA-4 +49A/G and CTLA-4 -318C/T were not significantly different among patients with and without inhibitors. However, HA patients without inhibitors revealed that the Chinese population exhibited a higher +49G allele which is protective towards inhibitors development. Indian patients expressed a higher level of inhibitors titre. Patients without inhibitors showed statistical differences between ethnicity for both genotypes and allele frequencies of CTLA-4 +49A/G (P < 0.05). Conclusion: The mixed pattern of polymorphisms and cytokine profiles were observed in multi-ethnicity. This finding requires further verification with a larger sample size involving multicenter for further confirmation.